2017
DOI: 10.3390/ijerph14080916
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Green Space Quality and Accessibility—Evidence from a Southern European City

Abstract: Background: The provision of green spaces is an important health promotion strategy to encourage physical activity and to improve population health. Green space provision has to be based on the principle of equity. This study investigated the presence of socioeconomic inequalities in geographic accessibility and quality of green spaces across Porto neighbourhoods (Portugal). Methods: Accessibility was evaluated using a Geographic Information System and all the green spaces were audited using the Public Open Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(137 citation statements)
references
References 73 publications
5
129
2
1
Order By: Relevance
“…There were 29 included papers from the United States ; seven from Australia; six from England; five from Scotland; three from Germany; two from each New Zealand, Spain, and Canada; and one each from France, Portugal, and Denmark (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 29 included papers from the United States ; seven from Australia; six from England; five from Scotland; three from Germany; two from each New Zealand, Spain, and Canada; and one each from France, Portugal, and Denmark (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Four additional studies not only took a similar approach but also included a buffer zone around the geographical area . Other studies employed a kernel density approach, or a buffer zone around either a population weighted centroid, a geographical centroid, a participant's home, or a random point within a geographical area . Three studies used a combination of approaches …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suburbs of higher socio-economic advantage have significantly more overall vegetation cover, more private green cover (but slightly less public green cover), more street trees, higher plant species richness and vegetation abundance than areas of greater disadvantage [6,17,[27][28][29]. Hoffimann et al [30] found that green spaces in lower socio-economic areas raise more safety concerns, have more signs of damage, less equipment and fewer amenities (such as seating, toilets, cafes). It is unclear from the literature whether the green cover recorded in these studies includes urban agriculture or food production; however, given the definition of nature and the methodologies used (usually aerial surveys) it can be assumed that it is.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are essential prerequisites for urban environmental justice, particularly to the accessibility and usability of blue environments in the area (cf. Kuhlicke et al 2012;Kabisch & Haase 2014;Hoffimann et al 2017). We list here our three key findings and conclusions related to these results and illuminate questions on how this continuum can be altered, specifically with regard improving spatial planning of blue spaces from the perspective of distributive justice and the opportunities and means to pay more attention to the socio-cultural and demographic aspects relevant in promoting well-being and welfare through interaction with nature in urban areas.…”
Section: Discussionmentioning
confidence: 57%